Infection of the Urinary Tract and its Prevalence Among Children Presenting with Malnutrition - Sijad-Ur-Rehman, Bilal Noor, Muhammad Ishaq, Kaleem Ullah, Gule Lala, Romana Bibi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: UTIs are a common cause of acute illness in newborns and young children, affecting 8% of girls and 2% of boys by age seven, with a recurrence rate of 10% to 30%. A UTI is a serious condition that can develop into sepsis and other life-threatening consequences in children Objective: To assess the frequency of urinary tract infections in malnourished children. Material and Methods: The study included 241 patients from the Pediatric Department of Children Gajju khan medical collage Swabi. Pakistan. July 7, 2019 – January 7, 2020, All children had urine samples taken by urine bags and catheterization and forwarded to the hospital laboratory to test for UTIs. The same consultant microbiologist with at least five years of expertise supervised all laboratory studies. Results: As per frequencies and percentages for UTIs, 19 (7.88%) patients had UTIs. Conclusion: Given the high frequency of UTIs in children with severe malnutrition, additional research utilizing standardized microbiological approaches is essential. To support the treatment recommendations for UTIs in these children, using urine dipsticks and microscopy in conjunction with urine culture is critical.